2020
DOI: 10.1177/0974910120919023
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Capital Structure and Speed of Adjustment under Hyperinflation and Dollarization

Abstract: Economic challenges in Zimbabwe have resulted in firms being pushed out of their optimal leverage. Firms are faced with the need to move back to the optimal level of financing to improve their value. They tend to adjust quickly to the optimal level whenever failing to do so is costlier. This study employs a dynamic capital structure model to examine the determinants of optimal leverage and the speed of adjustment under a hyperinflation and dollarization period (2000–2016). The study shows that firms have an op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 73 publications
(96 reference statements)
1
6
0
Order By: Relevance
“…The empirical results are similar to that of Faulkender et al (2012) and Dierker et al (2019). They adjust quickly to the optimal level whenever failing to do so is costlier, in line with the static trade-off theory (Mbulawa et al 2020). Secondly, the estimates with the System GMM topology measure showed similar results as the DOLS measure, thus confirming robustness in the previous DOLS analysis.…”
Section: Conclusion and Implications Of Studysupporting
confidence: 81%
See 4 more Smart Citations
“…The empirical results are similar to that of Faulkender et al (2012) and Dierker et al (2019). They adjust quickly to the optimal level whenever failing to do so is costlier, in line with the static trade-off theory (Mbulawa et al 2020). Secondly, the estimates with the System GMM topology measure showed similar results as the DOLS measure, thus confirming robustness in the previous DOLS analysis.…”
Section: Conclusion and Implications Of Studysupporting
confidence: 81%
“…Subsequent work from Kim (2015) postulated that companies listed on the stock exchange of Korea adjusted leverage faster toward the target level in the economic expansion situation, consistent with the pecking order and market timing theories. More recently, Mbulawa et al (2020) confirmed that companies have optimal leverage, and there are costs of adjusting to this level of capital. Consistent with the STT and agency theory, all models' adjustment factors are higher under hyperinflation than under dollarization.…”
Section: 21mentioning
confidence: 92%
See 3 more Smart Citations